ANALYSIS OF PADDY FARMER’S SATISFACTION ON INSECTICIDE X IN PENDEM VILLAGE, JUNREJO SUB-DISTRICT, BATU CITY - Made Anggara Citra Retnanti; Ratya Anindita (Agricultural Socio-Economics Journal, 2018)
Satisfaction is a condition where the demand for the products received in accordance with consumers’ expectation. The purpose of this research is to analyze the paddy farmer's satisfaction on the insecticide used. Data collection was done by interview technique using questionnaire. The method of analysis used is the method of Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The respondents were 40 rice farmers. This study usesone of the insecticide brands used by rice farmers. From the IPA method, the result shows that on average the conformity rate is 91.4%. This indicates that the insecticide product is able to meet consumer expectations. The resultof the CSI method shows that the satisfaction level is 78.2%.